Characteristics and DBP formation of dissolved organic matter from leachates of fresh and aged leaf litter. (June 2016) - Jian, Qianyun; Boyer, Treavor H.; Yang, Xiuhong; Xia, Beicheng; Yang, Xin
Abstract: Dissolved organic matter (DOM) was leached from leaves of two trees commonly grown in subtropical regions, Pinus elliottii (commonly known as slash pine) and Schima superba (S. superba), and its degradation pattern and potential for forming disinfection byproducts (DBPs) were evaluated. The leaves were exposed in the field for up to one year before leaching. The DOM leached from slash pine litter contained on average 10.4 mg of dissolved organic carbon (DOC) per gram of dry weight; for S. superba the average was 37.2 mg-DOC/g-dry weight. Ultraviolet and visible light absorbance, fluorescence, and molecular weight analysis indicated that more aromatic/humic and higher molecular weight compounds are formed as leaf litter ages. A 4-component parallel factor analysis of the fluorescence data showed that the intensity of peaks related with protein-like components decreased gradually during biodegradation, while that of peaks attributed to humic-acid-like components increased continuously. Fresh slash pine leachates formed on average 40.0 μg of trihalomethane (THM) per milligram of DOC, while S. superba leachates formed 45.6 μg. THM formation showed peak values of 55.7 μg/mg DOC for slash pine and 74.9 μg/mg DOC for S. superba after 8 months of aging. The formation of haloacetonitrile (HAN) and trichloronitromethane (TCNM) increased with increasing leaf age, while chloral hydrate (CH) formation did not show such a trend. Specific UV absorbance showed some positive correlation with DBPs, but humic-acid-like and protein-like absorbance peaks correlated with CH and TCNM yields in only some leaf samples. Graphical abstract: Highlights: The leachates from leaves exposed to the field up to a year were characterized. Aged leaves leachate contained more aromatic and higher molecular weight compounds. Photo- and bio-degradation played different roles in changing the properties of leaves leachate. Formation potential of carbonaceous and nitrogenous DBPs changed as the leaves aged.